Transformasi Edukasi Keuangan melalui Metode Gamifikasi bagi Siswa SDN 11 Pemecutan Denpasar - Helmy Syakh Alam; Eka Grana Aristyana Dewi; I Putu Shava Jaya Wardhana; Putu Rakhe Prabha Buana; Joshua Kevin Wijaya; Jelita Elisabeth Maak; I Kadek Subakti Kesuma (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
In the face of increasing financial complexity, providing elementary school students with fundamental financial literacy knowledge has become more imperative. Financial literacy is an essential life skill, but traditional teaching methods may not capture student's attention. This community service project sought to improve financial literacy among students at SDN 11 Pemecutan, Denpasar, through the gamification method "LIFIN" (Literacy Financial) using the PALAR (Participatory Action Learning and Action Research) approach. A total of 65 sixth-grade students participated. A pre-test was conducted one week prior with 54 students, while 39 completed the post-test two months later. Analysis of the 39 matched students showed an improvement in correct answers from 51% to 84.6%, and 71.8% showed high engagement with gamification, proving that game-based financial literacy education provides an interactive and effective learning experience. SDN 11 Pemecutan has committed to adopting "LIFIN" regularly across all grade levels.